Attention to the problem of the inaccurate testing caused by virus mutation strains in clinical laboratory settings - Gao Yulu (Global Journal of Clinical Virology - Peertechz Publications, 2017)
A few virus strain mutations for many viruses can cause the problem of the inaccurate testing in clinical laboratory settings. Therefore, we put forward the following strategies and recommendations including re-examination using different methods or a comparative study or a parallel control study by different kits, and performing virus nucleic acid sequencing analysis if necessary. In recent years, in vitro diagnostic test for the virus has made significant progress [1]. From a methodological point of view, these diagnostic tools were more and more accurate and reliable, but there are still some problems that should be paid attention to, especially for the problem of the inaccurate testing caused by virus strain mutation in clinical laboratory settings. At present, the most common methods of virus testing in clinical laboratory settings include as following: serological diagnosis based on antigen or antibody such as ELISA [2-4], and nucleic acid test methods including PCR [5], RT-PCR [6, 7], real-time PCR [8-13], and molecular hybridization [14-16], etc. However, there may be different test results when different kits or test methods were used.